Pengenalan Aplikasi Buku Kas dalam Digitalisasi Akuntansi pada Toko Kelontong - Hidayatussholikhah, Nurul; Budiantara, Martinus (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In the current digital era, business actors are expected to adapt to technological developments in managing their businesses to be more effective and efficient. The purpose of this understanding of Micro, Small, and Medium Enterprises (MSMEs) in conducting simple accounting records using the Buku Kas application. This service is carried out in two locations, namely Mrs. Yani’s grocery store and Mrs. Ratmi’s grocery store. The obstacle faced by the two entrepreneurs is the lack of bookeeping and financial transaction records due to insufficient understanding of financial records recording. Therefore, training was conducted by introducing and explaining the features avaible in the Buku Kas application as well as how to record income and expenditure transactions. After practicing regularly, both entrepreneurs made good progress week by week and became more diligent in digital financial recording.